11. ASSESSMENT OF THE RESULTS OF CHANGE IN THE PAR INDEX (PEER ASSESSMENT RATE) AFTER TREATMENT OF CLASS II ANGLE MALOCCLUSION WITH MBT BRACKET SYSTEM AT THE DEPARTMENT OF ODONTO-STOMATOLOGY CAN THO UNIVERSITY OF MEDICINE AND PHARMACY (Vietnam Journal of Community Medicine, 2023)
Background: Analysis to evaluate occlusal changes is very important in assessing orthopedictreatment outcomes. There are many analytical methods based on measurements on plaster samplesbefore and after treatment, such as measuring the distance between teeth and width of jaw arch orbased on an occlusal index such as ICON, PAR index.Objectives: Evaluation of the change in PAR index (peer assessment rate) after treatment of Class IIAngle malocclusion with the MBT bracket system at the Department of Odonto-Stomatology, CanTho University of Medicine and Pharmacy.Materials and methods: The study was conducted on 31 patients with Class II Angle malocclusionat the Department of Odonto-Stomatology, Can Tho University of Medicine and Pharmacy. Thepatients were treated for orthodontic treatment of Class II Angle malocclusion. Evaluation oftreatment results according to PAR. Degree of change = PAR before treatment - PAR after treatmentResult: The PAR index (W) before treatment was 32.19 ± 13.84. Among the components of thePAR index (W), overbite has the highest score of 11.16 ± 8.12, and overbite has the lowest score of2.00 ± 1.55. The index that changed the most was the overbite, reduced by 10.65 points, improvedby 93.67% after treatment, and the crowding in the posterior teeth decreased by at least 0.65 points,improved by 40.89%.Conclusion: In the of PAR(W) after treatment, the occlusal components all had a great changeafter treatment, there was no component in the coefficient that did not improve, indicating that theocclusion is very well improved, good guarantee in terms of functionality and stability.
Keywords: PAR index, Class II Angle Malocclusion.